Recurrent malignant struma ovarii presenting as peritoneal carcinomatosis in the setting of an intact thyroid: A case report and review of the literature - Morgan Brown; Paulina Haight; Matthew Ringel; John Phay; Ashwini Esnakula; Jennifer Vazzano; Casey Cosgrove (Elsevier, 2024)
Malignant struma ovarii is an exceedingly rare pathology with a paucity of established criteria regarding management and surveillance with recommendations largely based on case reports and retrospective data. Many authors have supported stratification of malignant struma ovarii into low vs high-risk disease with more conservative management reserved for those deemed low-risk. Here we present a unique case of recurrent metastatic malignant struma ovarii after surveillance was undertaken in the setting of initially low-risk disease.